The Phonemic − Syllabic Comparisons of Standard Malay and Palembang Malay Using a Historical Linguistic Perspective - Arsillah, Novita (2013)
Penelitian ini merupakan penelitian linguistik historis yang berjudul The Phonemic − Syllabic Comparisons of Standard Malay and Palembang Malay Using a Historical Linguistic Perspective yang bertujuan untuk mengeksplorasi jenis perubahan suara dan untuk mengungkapkan distribusi fonem vokal dan konsonan yang ditemukan di Palembang Melayu. Penyelidikan ini menggunakan metode komparatif linguistik historis untuk membandingkan perubahan suara antara bahasa asal yaitu Melayu Standar dan bahasa keturunannya yaitu Palembang Melayu. Melayu Standar pada studi ini mengacu pada kamus Wilkinson tahun 1908. Para peserta penelitian ini adalah tujuh penutur asli Palembang Melayu yang berumur antara 20 sampai 40 tahun. Data dikumpulkan dari suara peserta yang tercatat selama percakapan kelompok dan wawancara. Rekaman suara kemudian ditranskripskan menjadi suara transkripsi. Penelitian ini menggunakan kerangka teori perubahan suara yang diusulkan oleh Terry Crowley pada tahun 1997 dan Lily Campbell pada tahun 1999. Temuan menunjukkan bahwa ada sembilan jenis perubahan suara yang ditemukan sebagai hasil, yaitu asimilasi (42,35%), lenition (20%), penambahan suara (3,53%), metatesis (1,18%), disimilasi (1,76%), normal suara perubahan (3,53%), split (13,53%), penaikan vokal (10,59%), dan monophthongisation (3,53%). Demikian, perubahan suara tersebut teruji muncul secara teratur dalam data. Hasil analisis juga menunjukkan bahwa distribusi kata-kata antara fonem vokal dan konsonan ditentukan berdasarkan tiga jenis posisi fonem, yaitu awal, tengah, dan akhir. Posisi ini diputuskan berdasarkan pada posisi kejadian dari fonem pada kata. Kata kunci: linguistik historis, Melayu Standard, Melayu Palembang, metode komparatif, perubahan suara, fonem. Abstract This study is a historical linguistic investigation entitled The Phonemic − Syllabic Comparisons of Standard Malay and Palembang Malay Using a Historical Linguistic Perspective which aims to explore the types of sound changes and to reveal the distributions of the vowel and consonant phonemes found in Palembang Malay. The investigation used a historical linguistic comparative method to compare the sound changes between an ancestral language Standard Malay and its descent language Palembang Malay. Standard Malay refers to the Wilkinson dictionary in 1908. The participants of this study are seven native speakers of Palembang Malay whose ages range from 20 to 40 years old. The data were collected from the voice of the participants which were recorded along group conversations and interviews. The voice recordings were then transcribed into voice transcriptions. This study applies the theoretical framework of sound changes which proposed by Terry Crowley in 1997 and Lily Campbell in 1999. The findings show that there are nine types of sound changes that were found as the results, namely assimilation (42.35%), lenition (20%), sound addition (3.53%), metathesis (1.18%), dissimilation (1.76%), abnormal sound changes (3.53%), split (13.53%), vowel rising (10.59%), and monophthongisation (3.53%). Therefore, the examined sound changes appeared regularly in the data. The analysis results also indicate that words distribution among vowel and consonant phonemes determined based on three types of phoneme positions, namely initial, middle, and final. These positions were decided based on the occurrences of the phonemes. Keywords: Historical linguistics, standard Malay, Palembang Malay, comparative method, sound change, phoneme.